Membawa Tempat-tempat dalam Cerita ke Kehidupan Nyata: Pengaruh Cerita Masa Kecil terhadap Niat Berkunjung ke Tempat-tempat dalam Cerita - Patria, Teguh Amor; Lusia, Erma; Pratiwi, Irma Indri Astri; Rumba, Rumba (Centre For Tourism Planning and Development, 2024)
This paper presents a study that aims at investigating relationship between childhood stories and intention to visit the places in the stories. It involved 145 Tourism college students in Indonesia who rated their answers to 17 statements on an e-questionnaire using a 5-point Likert scale. Findings of the study showed there is a significant relationship between childhood stories and intention to visit. However, despite respondents’ interest in visiting the places in their childhood stories, they still would consider visiting other places beyond the places in their childhood stories provided they have other options. The findings can contribute to the knowledge about the relationship between childhood experiences and adults’ attitudinal and behavioral patterns, and to the planning, development, and marketing for a specific tourist market segment. Future studies can consider exploring the 54.5% of unknown factors affecting respondents’ interest in visiting tourist destinations or attractions associated or related to their childhood stories, as well as the volume of this specific tourist market segment.